Impact of SARS-COV-2 Variants on the Infection Severity among Iraqi Patients - Ghazzi, Jinan J.; Fadhil , Hula Y.; Aufi , Iman M. (Iraqi Journal of Science, 2023)
Severe acute respiratory corona viruses (SARS-COVs) are a particular category of RNA viruses that have emerged as a potential danger to the human population, triggering epidemics and pandemics that have resulted in catastrophic human mortality. The SARS-CoV2, responsible for the COVID-19 pandemic that began on December 12, 2019 in Wuhan, China, has been linked to bats. A new SARS-CoV-2 variant appeared in late December 2020. Mutations with variants continued to appear until the time of this study. Thus, this study aimed to provide a local database among Iraqi patients about SARS-COV-2 variants as there have been very few local studies documenting its existence and its relationship with the progression and severity of infection. For this study 234 nasal swabs were collected from COVID-19 positive individuals between March 2021 to March 2022. RNA was extracted and tested by using real-time reverse transcriptase polymerase chain reaction (rRT-PCR) assay to confirm infection, and the variants were detected by using a special kit that stratified the characteristic mutations. Results showed the presence of Alpha, Beta or Gamma and Omicron variants in our population at the same time as their global spread at high rates with different severity of cases. It increased in severity during infections with wild type 26/32 (81.25%) and Alpha 82/109 (75.23%) variants but a high incidence of Beta or Gamma 28/38 (73.68%) and Omicron 35/46 (76.09%) variants within mild-moderate infections. Moreover, there was a significant increase in severity in older age groups than younger. Hence, we can conclude that most severe infections with SARS-COV-2 appeared in wild type and during the appearance of Alpha variant which provided a unique database of variants of COVID-19 circulating in the Iraqi population and also assisted in determining the severity of disease. More research is needed on this subject.